High energy-density and power-density thermal storage prototype with hydrated salt for hot water and space heating. (15th August 2019) - Li, T.X.; Xu, J.X.; Wu, D.L.; He, F.; Wang, R.Z.
Graphical abstract: Operation modes and performance of high energy-density and power-density latent heat thermal storage prototype with hydrated salt for hot water and space heating. Highlights: High energy-density and high power-density prototype for thermal energy storage. Performance evaluation for hot water supply and space air heating applications. Heating power for hot water supply higher than 50 °C is as high as 10.3–18.6 kW. Room temperature can keep 16–19 °C for space heating at outdoor temperature 5–10 °C. Energy storage density is 2.5 times higher than that of traditional water tank. Abstract: Thermal energy storage is a key technology to promote renewable energy application and utilization of off-peak electricity for space heating and hot water. Hydrated salt is one kind of promising phase change materials for thermal energy storage but it usually has the common drawbacks of phase separation, high supercooling degree and poor thermal conductivity as well as low power density due to slow charging & discharging rates. Here, we develop a high energy-density and high power-density latent heat thermal energy storage prototype with heat capacity of 7.0 kWh by employing modified sodium acetate trihydrate with the aim of solving the phase separation and supercooling degree problems. The overall performance of latent heat thermal energy storage system with the prototype is evaluated for two different applications: hot water supply and space heating. The experimental results showed that the high power-density thermal storage prototype has excellent thermal performance and its volumetric energy storage density is about 2.5 times higher than that of traditional water tank. The system energy efficiency is higher than 90% under different working conditions. For hot water supply mode, the average heating power is as high as 10.3–18.6 kW and hot water temperature can reach 50 °C at different inlet cold water temperatures varying between 7 and 25 °C. For spacing heating mode, the hot air temperature is higher than 40 °C and indoor room temperature can keep above 16–19.5 °C when the outdoor temperature ranges between 5 and 10 °C. The proposed prototype has the advantages of high energy-density thermal storage, high power-density energy supply, and fast charging & discharging rates for hot water and space heating.